2020
DOI: 10.2147/ott.s266596
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knockdown of Long Non-Coding RNA LOC100132707 Inhibits the Migration of Uveal Melanoma Cells via Silencing JAK2</p>

Abstract: Background/Objective Although lots of long non-coding RNAs (lncRNAs) have been demonstrated to be involved in carcinogenesis, the functions of numerous of lncRNAs remain unknown. Bioinformatics online database showed that lncRNA LOC100132707 was highly expressed in metastatic melanoma tissues, and its expression predicted a lower overall survival rate in melanoma patients. However, LOC100132707 function in uveal melanoma (UM) progression still remains unclear. In the present study, we aimed to elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…LOC100132707, now named PAXIP1-AS2 (PAXIP1 antisense RNA 2), was upregulated in tumors from metastatic patients in the TCGA cohort. In vitro assays showed it promoted cell migration and invasion by upregulating JAK2 (Janus kinase 2), while reduced expression of LOC100132707/PAXIP1-AS2 impaired tumorigenesis in vivo [282]. By re-analyzing expression data from the GSE22138 dataset [199], Yang et al reported decreased levels of ZNF667-AS1 [ZNF667 antisense RNA 1 (head to head)] in metastatic patients compared to non-metastatic UM patients; follow-up data from TCGA showed the association of the lncRNA with histological type, metastasis, recurrence, and death, with a poorer prognosis in the low expression group.…”
Section: Lncrnas With Prognostic Value In Ummentioning
confidence: 99%
“…LOC100132707, now named PAXIP1-AS2 (PAXIP1 antisense RNA 2), was upregulated in tumors from metastatic patients in the TCGA cohort. In vitro assays showed it promoted cell migration and invasion by upregulating JAK2 (Janus kinase 2), while reduced expression of LOC100132707/PAXIP1-AS2 impaired tumorigenesis in vivo [282]. By re-analyzing expression data from the GSE22138 dataset [199], Yang et al reported decreased levels of ZNF667-AS1 [ZNF667 antisense RNA 1 (head to head)] in metastatic patients compared to non-metastatic UM patients; follow-up data from TCGA showed the association of the lncRNA with histological type, metastasis, recurrence, and death, with a poorer prognosis in the low expression group.…”
Section: Lncrnas With Prognostic Value In Ummentioning
confidence: 99%
“…In the last few decades, researchers have focused their attention on the role of lncRNAs in carcinogenesis [ 106 ]. Moreover, lncRNAs were found to be involved in the regulation of a plethora of cancer-related processes in UM [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ]. Given the important contribution of lncRNAs to cancer progression, their potential application as circulating biomarkers has been investigated.…”
Section: Serum/plasma Circulating Long Rnas In Ummentioning
confidence: 99%
“…The lncRNA LOC100132707 is overexpressed in metastatic UM, and is correlated with the Janus kinase 2 (JAK2)/Signal Transducer and Activator of Transcription 3 (STAT3) pathway, which are signal transducers and activators of transcription. The activation of this signaling leads to migration and invasion [72].…”
Section: Oncogenic Lncrnas In Uveal Melanomamentioning
confidence: 99%